Productions of invisible: considerations about time and training of teachers - Alice Dalmaso; Deisi Sangoi (Universidade Federal de Santa Maria, 2013)
This paper aims to approach, even though in a briefly way, the subject of invention in the training of teachers. In order to do this, we will make a brief overview on Virgínia Kastrup contributions about this issue. One of the questions is the time - through Henri Bergson's duration concept and its using in training theme. From this point, we will try to deconstruct a view about the identity reference in contemporaneity toward to multiple and open ways of existence. In the inventive movements of the processuality, the time is considered as an expression of human being individuation. It means to last refer to an immediacy of being, of being time, which are modulable and mutant, always in a creation process. In a movement of building a body which leaves an identity reference - that is opposite of self-transformation - necessarily we report us to the relation between the idea of time as duration and the individuation principle by Gilberto Simondon. With these concepts and their possible resonance in the discussion about formative politics, we can develop a view over the invisible to training of teachers and over the learners and another ways of operating in the world. The invention as a lever direct us to a field of possibilities to conceive and experience another time (and space) which is producer of subjectivity, singularities and differences.